Peningkatan Pengetahuan Pentingnya Sertifikasi Halal Sebagai Strategi Peningkatan Daya Saing UMKM di Kabupaten Banjarnegara - M. Aris Pujiyanto; Fitri Adi Setyorini (MARHALADO : Jurnal Pengabdian kepada Masyarakat, 2023)
This journal discusses efforts to increase knowledge about the importance of halal certification as a strategy to increase the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in Banjarnegara Regency. Halal certification is a key factor in expanding market access and increasing consumer confidence. The aim of this research is to increase the understanding of the MSME group in Banjarnegara Regency regarding the basic concept of halal certification, its significance in the context of business competitiveness, and its positive impact on local economic growth. The method of increasing knowledge involves outreach activities and workshops directly to MSME groups. The results are expected to have a positive impact on increasing awareness and implementation of halal certification among MSMEs, which in turn will contribute to increasing competitiveness and economic growth in Banjarnegara Regency.